SGLT-2 inhibitors and GLP-1 receptor agonists for nephroprotection and cardioprotection in patients with diabetes mellitus and chronic kidney disease. A consensus statement by the EURECA-m and the DIABESITY working groups of the ERA-EDTA. Issue 2 (6th February 2019) - Sarafidis, Pantelis; Ferro, Charles J; Morales, Enrique; Ortiz, Alberto; Malyszko, Jolanta; Hojs, Radovan; Khazim, Khaled; Ekart, Robert; Valdivielso, Jose; Fouque, Denis; London, Gérard M; Massy, Ziad; et al.
Abstract: Chronic kidney disease (CKD) in patients with diabetes mellitus (DM) is a major problem of public health. Currently, many of these patients experience progression of cardiovascular and renal disease, even when receiving optimal treatment. In previous years, several new drug classes for the treatment of type 2 DM have emerged, including inhibitors of renal sodium–glucose co-transporter-2 (SGLT-2) and glucagon-like peptide-1 (GLP-1) receptor agonists. Apart from reducing glycaemia, these classes were reported to have other beneficial effects for the cardiovascular and renal systems, such as weight loss and blood pressure reduction. Most importantly, in contrast to all previous studies with anti-diabetic agents, a series of recent randomized, placebo-controlled outcome trials showed that SGLT-2 inhibitors and GLP-1 receptor agonists are able to reduce cardiovascular events and all-cause mortality, as well as progression of renal disease, in patients with type 2 DM. This document presents in detail the available evidence on the cardioprotective and nephroprotective effects of SGLT-2 inhibitors and GLP-1 analogues, analyses the potential mechanisms involved in these actions and discusses their place in the treatment of patients with CKD and DM.